Women in construction: hindrances that shorten the professional working life of female site engineers on construction sites in South Africa - Sangweni, Nondumiso (My University, 2015)
The issues relating to women in construction exist internationally and, over the years they have been analysed from affirmative action Piper (2002) to cultural beliefs Hopkins & McManus (1998) job satisfaction and development Dabke (2008) and perception and professional acceptance Perreault (1992) & Enshassia (2008). In South Africa, following studies have been analysed, Verway (2005) looked at comparative analysis between SA and USA women entrepreneurs in construction, Mjolo-Mncube (2005) analysed opportunities for women in housing and construction, Mahlobo (2006) looked at challenges faced by women contractors in housing construction. However, not much emphasis has been put around hindrances that shorten the professional working life of female site engineers on construction sites in South Africa. The study adopted qualitative research method. Fifteen female site engineers currently working on construction sites for different construction companies were selected for questionnaires and open ended interview questions. Major findings identified discrimination, construction culture, work-conflict, glass ceiling, under representation of women and impact of cultural beliefs to be the hindrances that shorten the professional working life of female site engineers on construction sites. To retain female site engineers in the construction industry, it is recommended that employers introduce flexible work schedule; introduce mentorship programs and give them the same opportunities as their male counterparts in order to create more diversity in the sector thus increasing creativity and efficiency. Keywords: construction, site, engineers, work-life balance, hindrances, women, culture.
A research report submitted to the Faculty of Engineering & Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Building (Project Management in Construction).
Keywords: Construction industry; South Africa; Women; construction workers; Building trades